Chimera Patterns of Synchrony in a Frustrated Array of Hebb Synapses - Botha, A. E.; Ansariara, M.; Emadi, S.; Kolahchi, M. R. (Frontiers in Computational Neuroscience, 2022)
The union of the Kuramoto--Sakaguchi model and the Hebb dynamics reproduces the Lisman switch through a bistability in synchronized states. We show that this union can also result in chimera patterns of synchrony. We characterize the chimera by studying the distribution of the modifiable Hebb synapses. We study the stability range of the chimera as the frustration is changed. We show how the uniformly synchronous state becomes unstable giving birth to chimeras, one with faster incoherent region, another with faster coherent sector. Introducing an impurity in the ensemble, with faster natural frequency, we show that the chimera is led by it. This control mechanism creates a history dependent dynamics.